Association of HIV infection and hospitalization among mpox cases: a systematic review and meta-analysis - Muhammed Shabil; Shilpa Gaidhane; R. Roopashree; Mandeep Kaur; Manish Srivastava; Amit Barwal; G. V. Siva Prasad; Pranchal Rajput; Rukshar Syed; Anoop Dev; Danish Kundra; Ambanna Yappalparvi; et al. (BMC Infectious Diseases)
Abstract Background Mpox is a viral zoonotic disease that has seen a resurgence in recent years, with outbreaks reaching beyond its traditional endemic zones in Central and West Africa to parts of Europe and North America. The relationship between human immunodeficiency virus (HIV) infection and mpox outcomes, particularly hospitalization rates, remains underexplored despite the known immunosuppressive effects of HIV. This systematic review and meta-analysis aimed to clarify the association between HIV infection and the likelihood of hospitalization in mpox cases. Methods A literature search was conducted through PubMed, Embase, Web of Science, Scopus, and the Cochrane Library up until August 10, 2024. The eligibility criteria focused on observational studies that evaluated hospitalization rates among mpox cases, distinguishing between HIV-positive and HIV-negative individuals. Newcastle-Ottawa Scale was used for evaluating study quality. The meta-analysis used a random-effects model to accommodate expected study heterogeneity using R software (V. 4.4). Results The search yielded 686 records, with 14 studies meeting the inclusion and exclusion criteria after screenings and full-text assessments. The pooled analysis revealed a 56.6% increased risk of hospitalization among HIV-positive mpox cases compared to HIV-negative individuals (95% CI: 18.0–107.7%). Notable heterogeneity (I² = 76%) was observed, likely reflecting variations in study settings and methodologies. Sensitivity analysis confirmed the robustness of these findings, and no significant publication bias was detected (Egger’s test p-value = 0.733). Conclusion HIV infection is associated with a statistically significant increased risk of hospitalization in mpox cases. There is a critical need for integrated care and enhanced surveillance, especially in populations with high HIV prevalence. Our findings emphasize the importance of ongoing research to better understand HIV and mpox co-infection and to refine management strategies for this vulnerable group. Future studies should focus on long-term outcomes and the effectiveness of various management strategies across different healthcare settings.